Pakistan People’s Party and Foreign Policy Priorities: (2008-2013): An Analysis - Riffat Mahmood; Dr. Rehana Saeed Hashmi (Journal of Political Studies, 2020)
Owing to the changing dynamics of state relations, scholarly attention has increased toward the domestic policy influence on foreign policy. In this regard, political parties are considered the main drivers in foreign policy formulation in parliamentary democracies. To comprehend the influence of the party on the agenda or formulation of governmental foreign policy, there is a need to examine the link between party manifesto and foreign policy priorities. The case of Pakistan People’s Party (PPP) would be under consideration during the period from 2008-2013. This is an attempt to explore the foreign policy priorities given in the manifesto of Pakistan People’s Party (2008) with its practical implementations. It is observed that dichotomy prevails between the manifesto and practical implementations of PPP’s performance. The government of PPP has remained unsuccessful to implement its foreign policy priorities in true letter and spirit as promised in the party manifesto.